Residues in TAP2 peptide transporters controlling substrate specificity - Momburg, Frank; Armandola, Elena A.; Post, Markus; Hämmerling, Günter J. (The journal of immunology, 1996)
The transporter associated with Ag processing (TAP) translocates peptides from the cytosol into the endoplasmic reticulum where they associate with MHC class I molecules. Two specificity patterns with regard to the C-terminal residue of transported peptides have been previously shown. While the u allele of rat TAP and the mouse TAP preferentially transport peptides with hydrophobic C-terminal residues, no such selection was reported for the a allele of rat TAP or for the human TAP. We were able to map two short stretches in rat TAP2, with two polymorphic residues each, that essentially control the differential peptide transport observed for the rat alleles by constructing several hybrids between rat TAP2a and TAP2u and co-expressing them with rat TAP1 in TAP-deficient T2 cells. The critical residues are located in putative cytoplasmic loops close to the membrane.